2020
DOI: 10.29309/tpmj/2020.27.03.3901
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of different obstetrical factors with hemoglobin level in pregnant females.

Abstract: Objectives: To assess the correlation of different obstetrical factors with the hemoglobin level in multiparous pregnant females in Taif KSA. Anemia in pregnancy is a multifactorial phenomenon, among which obstetrical factors like parity, previous H/O abortions, inter pregnancy interval, mode of delivery etc are frequently associated. Study Design: Observational study. Setting: Outpatient department in King Faisal Hospital (KFH), Taif, Saudi Arabia. Period: 1st June 2018 and 31st August 2018. Material & Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 14 publications
(17 reference statements)
1
2
0
Order By: Relevance
“…Our finding is consistent with the previous studies that indicated that a short interbirth interval increases the risk of anemia [7,8,11,[24][25][26][27][28]. In contrast, some studies showed that a short interbirth interval has no association with maternal anaemia [9,10,12,13]. The majority of the previous studies modelled interbirth interval as a categorical variable in regression cannot capture the nonlinear relationship between interbirth interval and many perinatal outcomes and may produce a biased estimate of the association [38,39].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our finding is consistent with the previous studies that indicated that a short interbirth interval increases the risk of anemia [7,8,11,[24][25][26][27][28]. In contrast, some studies showed that a short interbirth interval has no association with maternal anaemia [9,10,12,13]. The majority of the previous studies modelled interbirth interval as a categorical variable in regression cannot capture the nonlinear relationship between interbirth interval and many perinatal outcomes and may produce a biased estimate of the association [38,39].…”
Section: Discussionsupporting
confidence: 89%
“…However, the results of previous studies were inconsistent. Some studies found that the short interbirth interval is associated with increased maternal anaemia [7,8,11], while others found little evidence for a relationship between short interbirth interval and maternal anaemia [9,10,12,13]. Although the biological mechanisms by which short interbirth intervals may lead to maternal anaemia have not been fully elucidated [14], it has been suggested that micronutrient depletion may partially explain associations between a short interbirth interval and maternal anaemia [15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation